How Many Samples are Enough When Data are Unbalanced? - Mehmet Mendeş (Journal of Agricultural Sciences)
A crucial component of the design of a study is the number of participants or observations sample size required. Taking too many samples will waste time and resources, both in collecting and analyzing the data. On the other hand, taking too small samples can make the whole study meaningless or lead to errors in interpritation. Equal group sizes are preferable. But, this is not always the case in practice. The aim of this study is to clarify some of the key issues regarding sample size and power 80 % when data are unbalanced. For this aim, a simulation study was conducted. At the end of the 50,000-simulation trial it was seen that there are many different sample size combinations that make it possible to reach around 80% test power. On the other hand, as the numbers of observations were getting more different, we needed more observations to reach around 80 % test power. For instance, the test power we reached for the 16 observations in each group n=16:16:16 , total 48 observations, we can only reach with 72 observations when sample sizes were unequal n=12, 30, 30 and n=12: 24: 36 . As the variances were getting more heterogenous, the effect of unbalanced data on test power was getting more obvious